Progression of central nervous system disease from pediatric to young adulthood in sickle cell anemia. Issue 23 (December 2021) - Champlin, Grace; Hwang, Scott N; Heitzer, Andrew; Ding, Juan; Jacola, Lisa; Estepp, Jeremie H; Wang, Winfred; Ataga, Kenneth I; Owens, Curtis L; Newman, Justin; King, Allison A; Davis, Robert; et al.
Silent cerebral infarcts and arteriopathy are common and progressive in individuals with sickle cell anemia. However, most data describing brain lesions in sickle cell anemia are cross-sectional or derive from pediatric cohorts with short follow-up. We investigated the progression of silent cerebral infarct and cerebral vessel stenosis on brain MRI and MRA, respectively, by describing the incidence of new or worsening lesions over a period of up to 25 years among young adults with sickle cell anemia and explored risk factors for progression. Forty-four adults with sickle cell anemia (HbSS or HbSβ 0 thalassemia), exposed to chronic transfusions ( n  = 12) or hydroxyurea ( n  = 32), median age 19.2 years (range 18.0–31.5), received a screening brain MRI/MRA and their results were compared with a clinical exam performed during childhood and adolescence. We used exact log-rank test to compare MRI and MRA progression among any two groups. The hazard ratio (HR) and 95% confidence interval (CI) were calculated from Cox regression analyses. Progression of MRI and MRA occurred in 12 (27%) and 4 (9%) young adults, respectively, relative to their pediatric exams. MRI progression risk was high among participants with abnormal pediatric exams (HR: 11.6, 95% CI: 2.5–54.7) and conditional or abnormal transcranial Doppler ultrasound velocities (HR: 3.9, 95% CI: 1.0–15.1). Among individuals treated with hydroxyurea, high fetal hemoglobin measured in childhood was associated with lower hazard of MRI progression (HR: 0.86, 95% CI: 0.76–0.98). MRA progression occurred more frequently among those with prior stroke (HR: 8.6, 95% CI: 1.2–64), abnormal pediatric exam ( P  = 0.00084), and elevated transcranial Doppler ultrasound velocities ( P  = 0.004). Brain MRI/MRA imaging in pediatrics can identify high-risk patients for CNS disease progression in young adulthood, prompting consideration for early aggressive treatments.